2011
DOI: 10.5751/es-04176-160422
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Soil-Management Strategies for Climate Mitigation in the European Union: Maximizing “Win–Win” Solutions across Policy Regimes

Abstract: . 2011. Exploiting soil-management strategies for climate mitigation in the European Union: maximizing "win-win" solutions across policy regimes. ABSTRACT. The Intergovernmental Panel on Climate Change (IPCC) has identified a number of soil-management strategies that can be implemented to reduce GHG emissions. However, before deciding which of these strategies are most appropriate in any given situation, it is important to investigate how these strategies affect other aspects of sustainable development. For in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…A number of other methods are being actively promoted to sequester more carbon in soils, although there is little evidence of widespread application thus far. Incorporating more biomass into soils is promoted as a way of enhancing agricultural productivity by improving soil structure, fertility and water infiltration, as well as sequestering carbon (Henriksen et al 2011). Biochar -adding charcoal to soils -has a very active group of promoters (Kleiner 2009;Sohi et al 2009).…”
Section: Risks To Groundwater From Carbon Sequestrationmentioning
confidence: 99%
“…A number of other methods are being actively promoted to sequester more carbon in soils, although there is little evidence of widespread application thus far. Incorporating more biomass into soils is promoted as a way of enhancing agricultural productivity by improving soil structure, fertility and water infiltration, as well as sequestering carbon (Henriksen et al 2011). Biochar -adding charcoal to soils -has a very active group of promoters (Kleiner 2009;Sohi et al 2009).…”
Section: Risks To Groundwater From Carbon Sequestrationmentioning
confidence: 99%
“…However, because all soil threats are applicable to agricultural productivity (Figure 1), it is crucial to target reductions in all soil threats to maintain and improve this soil function in the future. In addition, contrary to the targets of the Renewable energy Directive, the analysis of its implementation has shown that it creates trade-offs that compromise soil quality and reduce the soil function of biomass production in the long run [51].…”
Section: Soil Function 1: Food and Biomass Productionmentioning
confidence: 99%
“…However, an analysis of the CAP by Henriksen et al [51] reports that although GAEC is an important component to encourage soil management practices for mitigating carbon stocks, there are failures of implementation in Member States. The Renewable energy Directive addresses the soil carbon pool by allowing land conversion for biofuel production only if the loss of soil carbon stock that is caused by conversion can be remediated by savings in greenhouse gas emissions that accrue from biofuel production within a reasonable period.…”
Section: Soil Function 6: Carbon Poolmentioning
confidence: 99%
“…Henrikson, Hussey, and Holm (2011) explore the potential of soil management to address both energy and water conservation issues directly. Hitherto, soil has been identified as an important carbon sink, and the Intergovernmental Panel on Climate Change (IPCC) has identified a number of soil-management strategies that can be implemented to reduce greenhouse gas emissions.…”
Section: The Holy Grail: Systems Thinking and Policy Integrationmentioning
confidence: 99%